THE TERITORIAL PEDAGANG PADA PEDESTRIAN JALAN TEUKU HAMZAH BENDAHARA - Berutu, Iqbal Rifa'i Berutu; Hassan, Soraya Masthura; Andriani, Dela (JURNAL PERSPEKTIF ARSITEKTUR, 2024)
Changes that occur in urban or rural environments are dynamic and natural processes. They include physical, territorial and cultural changes, which are interrelated and influence each other. This paper will focus on the territorial aspect of the transformation. Pedestrian is one of the important elements in the development of a city. Pedestrians in the form of sidewalks are needed by pedestrians to avoid pedestrians walking on asphalt full of vehicles that can endanger pedestrians. Territory can be formed anywhere and anytime, including on the pedestrian. The formation of territory on the pedestrian is something that should not happen because the pedestrian is public and can be used by anyone and from any circle. This phenomenon often occurs in public spaces that are not optimally used so that there is a diversion of functions. The way territories are formed also varies from case to case, some ask for permission to form territories and some are directly formed without asking for permission. The signs and boundaries of the territory are also different for each territory owner, so to find out, observations and interviews must be conducted.